2014
DOI: 10.1016/j.chom.2014.09.006
|View full text |Cite
|
Sign up to set email alerts
|

The ER-Associated Protein ZDHHC1 Is a Positive Regulator of DNA Virus-Triggered, MITA/STING-Dependent Innate Immune Signaling

Abstract: Viral DNA sensing within the cytosol of infected cells activates type I interferon (IFN) expression. MITA/STING plays an essential role in this pathway by acting as both a sensor for the second messenger cGAMP and as an adaptor for downstream signaling components. In an expression screen for proteins that can activate the IFNB1 promoter, we identified the ER-associated protein ZDHHC1 as a positive regulator of virus-triggered, MITA/STING-dependent immune signaling. Zdhhc1(-/-) cells failed to effectively produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
125
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 133 publications
(134 citation statements)
references
References 40 publications
3
125
0
1
Order By: Relevance
“…Many host cell factors have been reported to regulate HSV-1 replication and/or pathogenicity in the CNS, as determined using experiments performed in genetically modified mice (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47). Notably, most of the host cell factors identified were regulators of innate and/or acquired immunity (33)(34)(35)(36)(37)(39)(40)(41)(42)(43)(44)(45)(46)(47).…”
Section: G and I) In Addition Increased Levels Of Neutrophil-likmentioning
confidence: 99%
“…Many host cell factors have been reported to regulate HSV-1 replication and/or pathogenicity in the CNS, as determined using experiments performed in genetically modified mice (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47). Notably, most of the host cell factors identified were regulators of innate and/or acquired immunity (33)(34)(35)(36)(37)(39)(40)(41)(42)(43)(44)(45)(46)(47).…”
Section: G and I) In Addition Increased Levels Of Neutrophil-likmentioning
confidence: 99%
“…This resource is now available for further studies. Another study demonstrated that STING constitutively interacts with the ER-associated protein ZDHHC1 and that this interaction is essential for STING dimerization and the recruitment of TBK1 (58). Finally, it has been reported that a series of cysteines in the membrane-spanning regions of STING are essential for IFN-␤ induction (59).…”
Section: Recognition Of Dnamentioning
confidence: 99%
“…Gapdh was used as a reference gene. Gene-specific primer sequences were described previously (11,30). The following primers were used for qPCR analysis of mouse Trim38 mRNA: 59-TGCTGGCGCTGTTATTGGG-39 (forward) and 59-GTTCACGCAATTTTGTCATGGT-39 (reverse).…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%